Development of NbTi planar superconducting undulators at the IHEP - Wei, Junhao; Yang, Xiangchen; Chen, Zilin; Zhang, Xiangzhen; Bian, Xiaojuan; Li, Yuhui (Frontiers in Physics, 2023)
Superconducting undulators (SCUs) have the advantages of generating stronger magnetic field and the radiation hardness compared to permanent magnet undulators. Therefore, SCUs are valuable to be applied in the free-electron lasers (FELs) driven by high-repetition-rate linear accelerators. The Insertion Device Group at the Institute of High Energy Physics (IHEP) in China started an R&D project to produce NbTi planar SCU prototypes with 15 mm period length. Several SCU prototypes, including short mock-ups, a 0.5-m-long SCU, and a 1.5-m-long SCU, have been successfully produced and cryogenic tested. The short mock-up coils were cooled by a liquid helium free cryostat to be quench trained at 4 K. The maximum current in the coils reached 500 A and the magnetic peak field exceed 1 T with 7 mm gap. The 0.5-m-long SCU was tested by using a vertical test system. The correction coils were confirmed with the ability in both correcting the magnetic field integrals and the phase error. The 1.5-m-long SCU was not only vertically tested, but also installed in a cryostat to be operated with high current over a long time. We applied the gap adjustment method to reduce the phase error within 9 degrees. The development of SCUs at the IHEP is introduced in this paper in detail.